Introduction to tourism transport - Gross, Sven, 1969-; Klemmer, Louisa (Boston CAB International, 2014)
Transport is an inherent part of tourism; whether as a functional means of transportation, such as between origin and destination or within the destination; or as a key element of the holiday experience itself, as in cruising or travelling along scenic or historic routes. Dealt with only superficially in many textbooks, this book addresses the imbalance affecting the transport side of tourism, and gives due consideration to this integral part of the industry. Providing the necessary background information to gain a comprehensive understanding of transportation markets, this book explores in detail each of the three modes of transportation - air, ground and water-based. Each section includes definitions, the historical development of the market and international institutional frameworks to provide a comprehensive review of the area. With the incorporation of case studies, learning objectives and further readings, this book facilitates an active learning process for students studying tourism and tourism transportation.
Includes bibliographical references and index.
Keywords: Tourism; Transportation